2019
DOI: 10.1186/s12906-019-2604-7
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and nephroprotective activity of Juglans mollis against renal ischemia–reperfusion damage in a Wistar rat model

Abstract: Background Oxidative stress and the inflammatory process are involved in ischemia–reperfusion (I/R) injury. Juglans mollis has been reported as having antioxidant activity, which could attenuate the damage caused by I/R. We evaluated whether a methanolic extract of Juglans mollis (JM) exhibits nephroprotective activity in a Wistar rat model of I/R injury. Methods Four groups of six rats were used: Sham, I/R, JM, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 51 publications
1
10
0
4
Order By: Relevance
“…Periods of ischemia of 45 min ( Kang et al, 2005 ) and 60 min ( Nakagawa et al, 2005 ) have been widely reported in the literature. We decided to use a protocol of 45 min of ischemia and 15 h of reperfusion based on the results of previous studies in our laboratory, which have shown that this protocol causes a significative injury, but is mild enough to identify compounds with moderate nephroprotective activity, allowing us to study deeply their potential pharmacologic activity ( Cura-Esquivel et al, 2018 ; Perez-Meseguer et al, 2019 ; Torres-González et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Periods of ischemia of 45 min ( Kang et al, 2005 ) and 60 min ( Nakagawa et al, 2005 ) have been widely reported in the literature. We decided to use a protocol of 45 min of ischemia and 15 h of reperfusion based on the results of previous studies in our laboratory, which have shown that this protocol causes a significative injury, but is mild enough to identify compounds with moderate nephroprotective activity, allowing us to study deeply their potential pharmacologic activity ( Cura-Esquivel et al, 2018 ; Perez-Meseguer et al, 2019 ; Torres-González et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Renal IRI, which contributes greatly to AKI, is one of the most critical issues for many clinical situations, including renal transplantation, nephrectomy, sepsis, and repair of suprarenal aneurism [ 129 131 ]. Hu et al [ 132 ] used a microarray assay to find that 2218 genes are differentially expressed in renal IRI, including 1103 upregulated genes and 1115 downregulated genes.…”
Section: Lncrna/circrna-mirna-mrna Axis In Irimentioning
confidence: 99%
“…Similarly, Cong G et al (24) as well as Hong X et al demonstrated an increase in SOD, GSH-Px and CAT activity in treatment groups using a polysaccharide from the roots of Dipsacus asperoides (25). Moreover, Gawel S et al (26) reported that luteoline increases SOD and CAT activity in RIR injury, suggesting that luteolin reduces RIR injury and oxidative stress (27). Taking all into consideration, the fi ndings of our study are consistent with previous studies such that SOD and GSH-Px activities are higher in ambrisentan and bosentan groups compared to the control group.…”
Section: Tab 3 Biochemical Alterations After Renal Ischemia Reperfusion In a Rat Modelmentioning
confidence: 88%
“…Both Aboutaleb N et al (23) and Hong X et al (25) found elevated MDA levels in untreated ischemia groups. Furthermore, in their study investigating the effect of Juglans mollissin on renal ischemia reperfusion injury, Perez-Meseguer J et al (27) reported that only MDA level in the treatment group is lower compared to that in the ischemia reperfusion group. Similar to previous studies, MDA levels in our study were found to be lower in both abrisentan and bosentan groups as compared to the control group although the differences among the groups did not reach the level of signifi cance.…”
Section: Tab 3 Biochemical Alterations After Renal Ischemia Reperfusion In a Rat Modelmentioning
confidence: 98%